Weber’s Law as the emergent phenomenon of choices based on global inhibition - Penconek, Marcin (Frontiers in Neuroscience, 2025)
Weber’s Law states that the ability to recognize the difference in intensity values is proportional to the reference intensity. The law is often generalized to the ratio principle which states that the proportionality also holds above the discrimination threshold. Experimental data showed that Weber’s Law fundamentally held in many sensory modalities including vision, audition, pressure, smell, and taste. However, violations were observed in many experimental studies and showed the mild convex relationship between stimulus intensities and Weber fractions. The magnitude of deviations from Weber’s Law was especially high in the low-intensity range in experiments on light brightness. The mechanistic foundation of Weber’s Law has recently received interest from neuroscience. It was postulated that the law constituted the emergent phenomenon arising in the choice circuit computing categorical choices based on global inhibition. This hypothesis suggested that the neurophysiological basis for Weber’s Law was linked to choice probabilities of a correct decision using linearly encoded stimulus intensities. Previous studies showed that the postulated mechanism led to the emergence of Weber’s Law. Our study showed that the same mechanism could also be responsible for the mild violation of Weber’s Law. The law approximately held for near-threshold discrimination, but did not hold as the ratio principle for easy discrimination with the high probability of a correct response. The revealed violation was qualitatively consistent with the experimental studies which showed the convexity of the relation between stimulus intensities and Weber fractions. However, the mechanism did not explain the magnitude of the deviations from Weber’s Law in the low-intensity range.